An advanced co-culture model of the human blood-cerebrospinal fluid barrier for separate analysis of choroid plexus epithelium and endothelium - Stump-Guthier, Carolin; Muranyi, Walter; Hagmann, Michael; Ishikawa, Hiroshi; Schroten, Horst; Schwerk, Christian; Weichert, Stefan (JoVE journal. Neuroscience, 2025)
The highly perfused choroid plexus (CP), located in the ventricular system of the brain, consists of several structural components, including a cuboid epithelium and a fenestrated endothelium, and is the location of the blood-cerebrospinal fluid barrier (BCSFB). To investigate the CP in vitro, several different cell culture setups are conceivable. An inverted cell culture filter model with strong barrier function, based on human epithelial CP papilloma (HIBCPP) cells, was established by our laboratory and is used extensively. Recently, we were able to generate a stable immortalized human CP endothelial cell line (iHCPEnC). Combining both cell lines, we have assembled an advanced functional two-cell-type model that developed an increased barrier function compared to HIBCPP cells alone. Since this model represents both the CP epithelium and endothelium, it allows for the investigation of the interplay between the two cell types under selected conditions, such as infection, inflammation, or others. In this protocol, we describe methods to set up this two-cell-type model with subsequent separation of the epithelial and endothelial cells for transcriptional analyses. We describe PCR primers specific for epithelium and endothelium, which serve to detect possible cross-contamination between the two cell types. To investigate a possible impact of the CP endothelium on the epithelium in this model under inflammatory conditions, the expression levels of selected genes in the context of lipopolysaccharide (LPS) treatment were analyzed in the HIBCPP cell fraction. The advanced CP in vitro model and the possibility to separately analyze epithelial and endothelial responses are of significant interest for research on cellular processes involving biological and pathological functions of the CP.